Predictive Factor for COVID-19 Worsening: Insights for High-Sensitivity Troponin and D-Dimer and Correlation With Right Ventricular Afterload - Goudot, Guillaume; Chocron, Richard; Augy, Jean-Loup; Gendron, Nicolas; Khider, Lina; Debuc, Benjamin; Aissaoui, Nadia; Peron, Nicolas; Hauw-Berlemont, Caroline; Vedie, Benoit; Cheng, Charles; Mohamedi, Nassim; et al. (Frontiers in Medicine, 2020)
Background: Coronavirus disease 2019 (COVID-19) has been associated with cardiovascular complications and coagulation disorders. Objectives: To explore clinical and biological parameters of COVID-19 patients with hospitalization criteria that could predict referral to intensive care unit (ICU). Methods: Analysing the clinical and biological profiles of COVID-19 patients at admission. Results: Among 99 consecutive patients that fulfilled criteria for hospitalization, 48 were hospitalized in medicine ward, 21 were first admitted to medicine ward and referred later to ICU and 30 were directly admitted to ICU from the emergency department. At admission, patients requiring ICU were more likely to have lymphopenia, decreased SpO2, a D-dimers level above 1000 ng/mL and a higher high-sensitivity cardiac troponin (Hs-cTnI) level. A receiver operating characteristic curve analysis identified Hs-cTnI above 9.75 pg/mL as the best predictive criteria for ICU referral (AUC 86.4, 95% CI 76.6–96.2). This cut-off for Hs-cTnI was confirmed in univariate (OR 22.8, 95% CI 6.0–116.2) and multivariate analysis after adjustment for D-dimers level (adjusted OR 20.85, 95% CI 4.76–128.4). Transthoracic echocardiography parameters subsequently measured in 72 patients showed an increased right ventricular (RV) afterload correlated with Hs-cTnI (r =0.42, p=0.010) and D-dimers (r=0.18, p=0.047). Conclusion: Hs-cTnI appears to be the best relevant predictive factor for ICU referring COVID-19 patients to ICU. This result associated with the correlation of D-dimers with RV dilatation probably reflects a myocardial injury due to an increased RV wall tension. This reinforces the hypothesis of a COVID-19-associated microvascular thrombosis inducing a higher RV afterload.